2005
DOI: 10.1002/jcb.20320
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the testis-specific histoneH1t gene by RFX2 may require both proximal promoter X-box elements

Abstract: The rat testis-specific linker histone H1t gene is transcribed in pachytene primary spermatocytes during spermatogenesis. Our previous work using transgenic mice demonstrated that spermatocyte-specific transcription of the H1t gene is dependent upon a proximal promoter element designated the TE element. TE is composed of two adjacent and inverted imperfect repeat sequences designated TE1 and TE2 and both of these palindromic elements are similar in sequence to the X-box, a DNA consensus sequence that binds reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The particular species identified in this report is the somatic factor RFX1, although other members of this family, including RFX2 and RFX4, are testis-specific (17,18). RFX sites are present in the germ cell-specific H1t gene, and RFX2 activates H1t expression in GC-2spd germinal cells (25,40). In this report, we did not further evaluate the role of this factor for ALF expression.…”
Section: Discussionmentioning
confidence: 82%
“…The particular species identified in this report is the somatic factor RFX1, although other members of this family, including RFX2 and RFX4, are testis-specific (17,18). RFX sites are present in the germ cell-specific H1t gene, and RFX2 activates H1t expression in GC-2spd germinal cells (25,40). In this report, we did not further evaluate the role of this factor for ALF expression.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, RFX proteins contain a conserved 76-residue WHD, whose crystal structure is similar to the WHDs of linker histones H1 (Gajiwala et al 2000). RFX2 binds specifically to these elements to activate transcription of the H1t gene in primary spermatocytes and both elements appear required for maximal promoter activity (Grimes et al 2005;Horvath et al 2004;Wolfe et al 2004). In comparison to other RFX proteins, RFX2 is preferentially expressed in testis, being most abundant in spermatocytes where transcription of H1t is upregulated (Horvath et al 2004;Wolfe et al 2006).…”
Section: Transcriptional and Translational Regulationmentioning
confidence: 97%
“…RFX2 is a crucial factor required for spermatogenesis, but the exact role for RFX2 in the control of cilia assembly is poorly understood (Grimes et al, 2005; Horvath et al, 2004; Horvath et al, 2009; Kistler et al, 2009; Liu et al, 2007; VanWert et al, 2008; Wolfe et al, 2004; Wolfe et al, 2006; Yu et al, 2008). Nonetheless, RFX2 has been shown to be expressed in some ciliated tissues (Hellman et al, 2010; Liu et al, 2007; Ma and Jiang, 2007) and its expression was reported to be controlled by another ciliogenic transcription factor, FoxJ1 (Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%